Apremilast Coadministered with Secukinumab for Safe and Effective Control of Psoriasis with Resultant Reduction of Maintenance Dose of the Biologic - De, Abhishek (Indian J Dermatol, 2019)
Psoriasis is a chronic immune-mediated inflammatory condition, affecting 2–3% of the population. In recent years, advent of biologics, including secukinumab, have been a major advancement in the management of difficult-to-treat plaque psoriasis. However, high cost of biologics is often a deterrent, especially for Indian socioeconomic condition. Apremilast is an oral phosphodiesterase 4 inhibitor that is safe for use along with many other systemic therapies of psoriasis, including biologics. We report two cases of psoriasis on secukinumab therapy for long duration with good response to therapy. Later, addition of apremilast, allowed halving the dose of secukinumab with maintenance of improvement.